2009
DOI: 10.1243/17543371jset33
|View full text |Cite
|
Sign up to set email alerts
|

Does a virtual audience influence rowing?

Abstract: The performance of athletes is often influenced by the presence of an audience. This pressure situation, which is common for competition, cannot be trained for on available simulators. Therefore, a novel rowing simulator with virtual reality technology was developed and evaluated. Ten participants of different skill levels were rowing 3 • 1000 m with positive, neutral, and negative virtual audience tribunes in blocks of random order. The analysis of movement variables, physiological response, questionnaires, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Examining the differences between the two they concluded that both with respect to questionnaire and biomechanical responses that the methods were similar enough for the simulator to be used as a complementary training tool, since there was sufficient and appropriate transfer of training using this method. Wellner et al (2010b) described an experiment where 10 participants took part in simulated rowing. The novelty was that they added a virtual audience to test the idea that the presence of an audience would encourage the rowers in a competitive situation.…”
Section: Sportsmentioning
confidence: 99%
“…Examining the differences between the two they concluded that both with respect to questionnaire and biomechanical responses that the methods were similar enough for the simulator to be used as a complementary training tool, since there was sufficient and appropriate transfer of training using this method. Wellner et al (2010b) described an experiment where 10 participants took part in simulated rowing. The novelty was that they added a virtual audience to test the idea that the presence of an audience would encourage the rowers in a competitive situation.…”
Section: Sportsmentioning
confidence: 99%
“…Experimental research in Virtual Reality (VR) has a lot of potential in different research fields such as experimental brain research, psychology (McClernon et al, 2011 ) and sports (Wellner et al, 2010 ). Among its advantages, VR minimizes disturbances in complex experiments involving multiple subjects or intricate experimental protocols.…”
Section: Introductionmentioning
confidence: 99%
“…One earlier study was conducted with the same setup using three types of audience, inspired by a study on public speaking anxiety (Pertaub et al, 2002). But in contrast to the findings there, audience pressure resulted in few behavioral changes in rowing (Wellner, Sigrist, von Zitzewitz, Wolf, & Riener, 2010). The current study used the illusion of competitors which was supposed to create a stronger feeling of pressure and therefore more pronounced behavioral changes.…”
Section: Related Workmentioning
confidence: 97%
“…We previously assessed the use of psychophysiological variables in a similar study with a virtual audience (Wellner et al, 2010), but we found that these variables responded more to exercise than to psychological changes.…”
Section: Lessons Learnedmentioning
confidence: 99%